Dynamics of the freshwater ichthyofauna diversity in the Late Miocene of the Southern Ukraine - Kovalchuk О.М.; Emelyanov, I.G. (Reports of the National Academy of Sciences of Ukraine, 2015)
The ecological characteristics of the Late Miocene freshwater fish assemblages of the Southern Ukraine are studied. The taxonomic analysis of the late Sarmatian, Meotian, and Pontian ichthyocomplexes from 24 fossil-bearing strata of 20 localities has been carried out. Taxonomic complexity of the Late Miocene bony fish assemblages is estimated, and the comparison of their faunistic composition with oryctocenoses close by age on the territory of Europe and Asia is presented.